CHURCH AND SCHOOL – BIRTALAN JÓZSEF’S CREDO - FODOR, Attila (Studia Universitatis Babes-Bolyai Musica, 2019)
József Birtalan is one of the prominent personalities of the Transylvanian music education and choral culture of the 20th century. The present study proposes to summarize his aesthetic motivations as a composer, conductor and pedagogue through a paradigmatic choir work, based on the well-known poem of the Transylvanian poet Reményik Sándor: Church and school. It is not only one of his most important works, but also one of the Transylvanian choral music, both in aesthetic and musical sense. Its passionate atmosphere and ideological depth reflect his author continuous aspirations as an artistic credo: the promotion of the musical mother tongue through the folk and church music, and so, the affirmation of his cultural identity.